Pirólise da casca de buriti e ativação térmica de seu carvão vegetal para uso como adsorvente na adsorção do Cobre II - ESQUERDO, Larissa Tavares (2019)
This work aims to peel the fruit, pyrolysis residue from processing the buriti Mauritia Flexuosa, for production of charcoal, your thermal activation and characterization of charcoal and activated carbon obtained at different temperatures, as well as the performance of the adsorption process. Pyrolysis was held on muffle oven the temperature of 800° C, then the product obtained was cominution and subjected to thermal activation process in times of 1, 2 and 3 hours, respectively, with the purpose to carry out thermal activation of charcoal. Activated charcoal obtained was subjected to adsorption tests for 60 min using a solution of Cu (II) to promote the contact and the adsorption of Cu (II) adsorbate by activated carbon and also to evaluate the adsorption capacity of activated coals produced. The quality of the activated charcoal depends on the activation time, fixed carbon, density and ash content suitable for the porosity of the material. In this way, the charcoal and activated carbon were obtained was characterized through analysis on SEM, XRD, EDS and FRX and adsorption test solutions were analyzed by Atomic absorption spectrophotometry AAS. Based on these characterizations, the best activated carbon produced was that of 1:00. This is evident in the results of the chemical composition, where she performed as featured in the calculations of income (60%), volatile material (40%), ash content (7.38%) and fixed carbon (52.62%), as well as the other characterizations of (SEM-EDS), in which the morphology was able to identify the presence of pores in the homogeneous form between the substances (CACB1h, CACB2H, CVCB and CACB3H), where this is the case with porous opening elimination of volatile material and is proportional to the time of activation; Furthermore, spectrum analysis confirmed the presence of the element carbon (C) in your composition. It was found by analyses of the FXR and DRX the presence of quartz and silvina, composition of coal characteristic of organic origin Soon, the bark of the buriti current as an interesting alternative to the production of activated carbon, helping in the reduction of impacts that such waste can generate in the environment.